2019
DOI: 10.1111/jnc.14725
|View full text |Cite
|
Sign up to set email alerts
|

The role of pericytes in brain disorders: from the periphery to the brain

Abstract: It is becoming increasingly apparent that disorders of the brain microvasculature contribute to many neurological disorders. In recent years it has become clear that a major player in these events is the capillary pericyte which, in the brain, is now known to control the blood–brain barrier, regulate blood flow, influence immune cell entry and be crucial for angiogenesis. In this review we consider the under‐explored possibility that peripheral diseases which affect the microvasculature, such as hypertension, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 270 publications
(664 reference statements)
0
24
0
Order By: Relevance
“…Pericytes are multifunctional mural cells located within the basement membrane of microvessels and adjacent to endothelial cells. Pericytes are abundantly present along the walls of brain microvasculature, including pre-capillary arterioles, capillaries, and post-capillary venules, and are a vital component of the neurovascular unit [ 70 ]. Studies have reported key roles of pericytes in the regulation of the BBB integrity, modulation of cerebral blood flow, central nervous system scarring, migration of white blood cells through the vascular wall, and promoting angiogenesis and clearance of cell debris [ 70 , 71 , 72 ].…”
Section: Endotheliummentioning
confidence: 99%
See 4 more Smart Citations
“…Pericytes are multifunctional mural cells located within the basement membrane of microvessels and adjacent to endothelial cells. Pericytes are abundantly present along the walls of brain microvasculature, including pre-capillary arterioles, capillaries, and post-capillary venules, and are a vital component of the neurovascular unit [ 70 ]. Studies have reported key roles of pericytes in the regulation of the BBB integrity, modulation of cerebral blood flow, central nervous system scarring, migration of white blood cells through the vascular wall, and promoting angiogenesis and clearance of cell debris [ 70 , 71 , 72 ].…”
Section: Endotheliummentioning
confidence: 99%
“…Additionally, diabetes-induced advanced glycation end-product formation enhances fibronectin production in pericytes with associated basement membrane hypertrophy and downregulates claudin-5 expression in microvascular CEC via VEGF and MMP2, thus promoting tight junction damage [ 76 ]. Moreover, kidney diseases can increase the rate of calcification and mineralization in pericytes and modify their function [ 70 ].…”
Section: Endotheliummentioning
confidence: 99%
See 3 more Smart Citations